2013
DOI: 10.1088/1751-8113/46/16/165202
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of the Liénard II equation and Jacobi’s last multiplier

Abstract: In this paper, the role of Jacobi’s last multiplier in mechanical systems with a position-dependent mass is unveiled. In particular, we map the Liénard II equation to a position-dependent mass system. The quantization of the Liénard II equation is then carried out using the point canonical transformation method together with the Von Roos ordering technique. Finally, we show how their eigenfunctions and eigenspectrum can be obtained in terms of associated Laguerre and exceptional Laguerre functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 45 publications
0
34
0
2
Order By: Relevance
“…In this section we will be specifically concerned with the quantized version of (21) and seek a solution of the corresponding Schrödinger equation having momentum-dependent mass and the potential function given in (22) in contrast to the coordinate-dependent mass situation that has been well studied in the literature [15,16,17,18,19] in the configuration space. In fact taking cue from such investigations we begin this section with a von Roos type of decomposition [20] for the generic Hamiltonian in the momentum space…”
Section: The Schrödinger Equation With a Momentum Dependent Massmentioning
confidence: 99%
“…In this section we will be specifically concerned with the quantized version of (21) and seek a solution of the corresponding Schrödinger equation having momentum-dependent mass and the potential function given in (22) in contrast to the coordinate-dependent mass situation that has been well studied in the literature [15,16,17,18,19] in the configuration space. In fact taking cue from such investigations we begin this section with a von Roos type of decomposition [20] for the generic Hamiltonian in the momentum space…”
Section: The Schrödinger Equation With a Momentum Dependent Massmentioning
confidence: 99%
“…Also, we have shown that if we replace the independent variable t with τ = it, then Equation (8) is transformed into Equation (20), which is one of the isochronous Liénard II equations [33]. Its corresponding Schrödinger equation was derived in [23,34]. The eigenfunctions and energy eigenvalues are given in (23) and (24), respectively.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…The quantization of Equation (21) was given in [34]. In [23], the quantization that preserves the Noether symmetries was applied to all equations (21).…”
Section: Quantizing With Noether Symmetriesmentioning
confidence: 99%
“…Our strategy now is to deduce a constant mass Schrödinger equation from (19) in the new coordinate variable g corresponding to the potential U(g) with the same energy eigenvalue E of the PDM system (17). It can be achieved by choosing…”
Section: Quantum Solvability Of Hermitian Hamiltonianmentioning
confidence: 99%
“…Other classes of nonlinear oscillators have also been studied in the context of PDM problem [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%